Laparoscopic cholecystectomy in an unsuspected left sided gallbladder: a rare case report with review of literature - Hajong, Ranendra (International Surgery Journal, 2024)
Left sided gallbladder (LSG) is a very rare clinical entity and most are diagnosed at operation. The patients usually present with features of biliary colic or pain in the right upper abdomen similar to normally positioned gallbladder. Ultrasonography is not a good diagnostic modality for diagnosing LSG and CT scan is better for the pre-operative diagnosis of the condition. Laparoscopic cholecystectomy can be done in patients with LSG and antegrade or fundus first technique is usually advocated.